Jesus' Spirituality of [Af]filiation in the Fourth Gospel - Lee, Dorothy A. (Religions, 2022)
The spirituality of Jesus, embedded within the literary contours of the Johannine narrative, is primarily grounded in a relationship of affiliation and friendship. It is a spirituality of abiding whose origins and goal lie in the unity of heart and mind that the Johannine Jesus as Son shares with the Father. This core relationship connotes not only the love that binds Jesus to God but is also the basis of the motif of sending and the divine authority over life and death which Jesus possesses in this Gospel. Jesus’ spirituality is grounded in the abiding presence of the Spirit-Paraclete whom he bequeaths to the disciples. In handing over the Spirit to the gathered community through his death and resurrection, Jesus donates his own spirituality, ultimately drawing all creation into the divine circle of love. This spirituality is the result of the Spirit’s presence, restoring human beings to their original, created identity as children and friends of God and empowering them for mission. While the dominant imagery is masculine there are also feminine images, particularly that of divine Wisdom, which provide a counterbalance and create an inclusive sense of appropriation and welcome.